2018
DOI: 10.1002/jper.18-0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress, serum and salivary cortisol, and interleukin‐1β levels in smokers and non‐smokers with chronic periodontitis

Abstract: The results indicate that smokers with CP exhibit a significantly higher serum and salivary cortisol, IL-1β, and stress levels and thus they may show an increased risk and periodontal disease severity. Further exploration of relationships between periodontitis and stress is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 46 publications
(70 reference statements)
5
28
0
Order By: Relevance
“…It showed a positive association of both with periodontal disease, which further confirms the findings of our study [ 28 ]. In another study, investigating the histo-pathogenesis of inflamed periodontium, revealed a significant increase in leukocyte (neutrophilic granulocytes 60% to 70%) under accumulated plaque with collagen-poor connective tissue at 4 days of infection (initial periodontitis) [ 29 ]. However, at 28 days of disease, the infiltrate comprised mainly of mononuclear leukocytes, especially plasma cells; and neutrophils occupied only a small fraction of the infiltrate [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed a positive association of both with periodontal disease, which further confirms the findings of our study [ 28 ]. In another study, investigating the histo-pathogenesis of inflamed periodontium, revealed a significant increase in leukocyte (neutrophilic granulocytes 60% to 70%) under accumulated plaque with collagen-poor connective tissue at 4 days of infection (initial periodontitis) [ 29 ]. However, at 28 days of disease, the infiltrate comprised mainly of mononuclear leukocytes, especially plasma cells; and neutrophils occupied only a small fraction of the infiltrate [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent investigations, osteoclastic bone damage was found to be directly related to the receptor activator of NF-kB ligand (RANKL) produced by osteoblastic cells and periodontal ligament cells. The induced periodontal inflammation triggers essential agents for RANKL induction that regulates osteoclast function and activity [ 29 ]. Hence, leading to bone loss in surrounding region and tooth mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Readings were repeated by the same examiner (VK) to perform intra-observer reproducibility analysis. [ 1 ]…”
Section: Methodsmentioning
confidence: 99%
“…The ongoing interactions involving microorganisms, host defense assembly, environmental and genetic factors have been known to influence the rate of progression and destruction, which leads to the clinical expression of disease. [ 1 ] If left uncontrolled, the disease in their severe forms precipitates progressive destruction, ultimately leading to tooth loss and edentulism. [ 2 ] Microorganisms, through an indirect mechanism, trigger different components within the host defense assembly, leading to the destruction of the periodontal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies [4][5][6][7][8] have assessed the relationship between the expression of cortisol in the gingival crevicular fluid (GCF) and whole saliva of patients with periodontitis, and their outcomes presented that GCF and whole salivary levels of cortisol are increased among patients with compared with individuals without periodontitis. [4][5][6][7][8] Anxiety and depression are often reported to influence the expression of cortisol in oral fluids (GCF and saliva) [4][5][6][7][8] ; however, it has also been proposed that the role of anxiety and depression in this regard is rather secondary. 9 Peri-implantitis is a local and usually site-specific inflammatory reaction, which manifests as increased crestal bone loss (CBL), plaque index (PI), bleeding on probing (BOP), and probing depth (PD).…”
Section: Introductionmentioning
confidence: 99%